Globalization the key concepts - Mooney, Annabelle 1974-; Evans, Betsy 1966- (Routledge key guides, 2007)
Viewed as a destructive force or an inevitability of modern society, globalization is the focus of a multitude of disciplines. A clear understanding of its processes and terminology is imperative for anyone engaging with this ubiquitous topic. Globalization: the Key Concepts offers a comprehensive guide to this cross-disciplinary subject and covers concepts such as: * homogenization * neo-Liberalism * risk * knowledge society * time-space compression * reflexivity. With extensive cross-referencing and suggestions for further reading, this book is an essential resource for students and interested readers alike as they navigate the literature on globalization studies.